Representation in the genome and in other inheritance systems - Shea, N (Springer, 2007)
There is ongoing controversy as to whether the genome is a representing system (Sterelny K., Smith K.C. and Dickson M. 1996. Biol. Philos. 11: 377-403; Griffiths P.E. 2001. Philos. Sci. 68: 394-412). Although it is widely recognised that DNA carries information, both correlating with and coding for various outcomes, neither of these implies that the genome has semantic properties like correctness or satisfaction conditions (Godfrey-Smith P. 2002. In: Wolenski J. and Kajania-Placek K. (eds), In the Scope of Logic, Methodology, and the Philosophy of Sciences, Vol. II. Kluwer, Dordrecht, pp. 387-400). Here a modified version of teleosemantics is applied to the genome to show that it does indeed have semantic properties - there is representation in the genome. The account differs in three respects from previous attempts to apply teleosemantics to genes. It emphasises the role of the consumer of representations (in addition to their mode of production). It rejects the standard assumption that genetic representation can be used to explain the course of an organism's development. And it identifies the explanatory role played by representational properties of the genome. A striking consequence of this account is that other inheritance systems could also be representational. Thus, a version of the parity thesis is accepted (Griffiths P.E. 2001. Philos. Sci. 68: 394-412). However, the criteria for being an inheritance system are demanding, so semantic properties are not ubiquitous.